PkM : Implementasi Pembelajaran Jarak Jauh di SMKN 9 Bandar Lampung - Erliyan Redy Susanto; Jupriyadi Jupriyadi; Dian Pratiwi (Universitas Teknokrat Indonesia, 2023)
The rapid spread of the COVID-19 pandemic worldwide has affected various aspects of human activities. Economic, social, educational, cultural, and religious activities have been impacted due to this virus. The Indonesian government has implemented various efforts to prevent the spread of the COVID-19 virus, including the implementation of social distancing among the population. Consequently, various activities have been restricted to suppress the transmission of the virus. Following the guidelines from the Minister of Education and Culture of the Republic of Indonesia, the traditional face-to-face classroom learning system has been changed to online learning. SMK 9 Bandar Lampung, a vocational high school, is facing challenges in distance learning, particularly due to the lack of an integrated online learning system and standardized guidelines for online education. Some teachers have been conducting classes using the WhatsApp application, while others are using the Google Classroom platform. The aim of this Community Service Program is to assist SMK 9 Bandar Lampung in addressing the challenges of integrated online learning. The Moodle platform is utilized to develop a distance learning system. The implementation of this program adopts an offline tutorial method in the form of practical sessions. The results of this program indicate an improvement in teachers' understanding of using tools in the distance learning system